Microbial Test-System for Screening of Inhibitors of Sterol Biosynthesis - A. S. Trenin (Антибиотики и Химиотерапия)
New effective economic microbial test-system for screening of microbial metabolites, that are inhibitors of sterol biosynthesis, is proposed. It is based on cultivation of fungal strain Acremonium fusidioides (former Fusidium coccineum), that produces fusidic acid (fusidin) that is antibiotic of steroid structure. Great similarity of fusidic acid biosynthesis in fungous strain and cholesterol biosynthesis in human organism, coincidence of their initial steps till squalene formation, allows use A. fusidioides as a model for estimation of microbial secondary metabolites that are potential inhibitors of sterol biosynthesis. Such inhibitors in A.fusidioides model are revealed as compounds that strongly reduce fusidin production without any visible influence on fungus growth. Mevalonate that is one of the crucial intermediates of sterol biosynthesis could be successfully applied for removal of inhibition induced by some microbial metabolites. A.fusidioides test-system can be easily mechanized because of miniaturization of microbiological procedures, cultivation in 6-, 24-, or 96-well plates and usage of automatic micropipettes and dispensers. The results of this model are well correlated with the ones obtained with human cells (Hep G2 test-system, offered earlier). A.fusidioides test-system can be applied at rather early stages of screening procedures and is quite effective for testing of crude extracts of producers' culture liquid.